ChemInform Abstract: Diastereodivergent Carbometalation/Oxidation/Selective Ring Opening: Formation of All‐Carbon Quaternary Stereogenic Centers in Acyclic Systems. Issue 40 (12th September 2013) - Delaye, Pierre‐Olivier; Didier, Dorian; Marek, Ilan
Abstract The developed title reaction sequence allows the preparation of both enantiomers of aldehyde (VIb) starting from the same initial cyclopropene derivative [(S)‐Ib].